SELF-EFFICACY AND CAREER GUIDANCE SERVICES AS PREDICTORS OF STUDENTS’ ACADEMIC ADJUSTMENT IN NSUKKA EDUCATION ZONE, ENUGU STATE (Cuestiones de Fisioterapia, 2025)
This study examined self-efficacy and career guidance services as predictors of students’ academic adjustment in Nsukka Education Zone, Enugu State. Three research questions and three null hypotheses guided the study. The study adopted a correlational research design. The population of the study comprised 4,382 Senior Secondary School Two (SS2) students in public secondary schools in Nsukka Education Zone, Enugu State. Using Krejcie and Morgan (1970) sample size determination table, a sample size of 351 students were sampled through multi-stage sampling procedure. Data were collected using three structured questionnaire titled, Self-Efficacy Questionnaire (SEQ), Career Guidance Services Questionnaire (CGSQ) and Academic Adjustment Questionnaire (AAQ). The instrument was validated by three experts, while its reliability was established using Cronbach Alpha method. The internal consistency of the instruments yielded reliability coefficients of 0.83, 0.88 and 0.87 for SEQ, CGSQ, and AAQ respectively. Data collected were analyzed using regression analysis. The hypotheses were tested at 0.05 level of significance. The findings of the study revealed that self-efficacy significantly predicts students’ academic adjustment and accounts for 20.7% of the variation in students’ academic adjustment in Nsukka Education Zone, Enugu State. The study also revealed that career guidance services significantly predict students’ academic adjustment and account for 14.7% of the variation in students’ academic adjustment. Furthermore, the findings showed that self-efficacy and career guidance services jointly account for 28.9% of the variation in students’ academic adjustment and significantly predict students’ academic adjustment in the study area. Based on the findings, it was concluded that self-efficacy and career guidance services are important determinants of students’ academic adjustment. It was therefore recommended, among others, that school counsellors should organize programmes aimed at improving students’ self-efficacy and that effective career guidance services should be strengthened in secondary schools to enhance students’ academic adjustment.